Effect of Site of Injection on Spread of Spinal Anaesthesia with Hyperbaric Bupivacaine - Karim, MA; Banik, Debasish; Huda, Qumrul; Hye, Abdul; Banik, Debabrata; Begum, Feroza (Bangladesh Journal of Obstetrics & Gynaecology, 2009)
Spinal Anaesthesia during caesarean section is popular world wide. The aim of the study was the explore the efficacy of spinal Anaesthesia with hyperbaric bupivacaine at different intervertebral space in lower uterine caesarean section. Ninety unpremeditated patients (20-40 years) undergoing caesarean section were allocated randomly to receive 0.5% hyperbaric bupivacaine 2ml at the site of L2-3, L3-4 and L4-5 intervertebral space. Spinal injection was performed to all patients with a 25-gauge Quincke spinal needle. The onset time of analgesia at T10 and T6 was significantly faster and the level of analgesia at 5 and 10 min was significantly higher after injection at L2-3. But the maximum height (T4) of analgesia at 15 and 20 min after injection and the number of episodes of hypotension were not significantly different among the three groups. So we can conclude that onset of Analgesia is altered by the site of injection, but the overall analgesia level achieved remain unchanged. Key words: Spinal anaesthesia, hyperbaric bupivacane, site of injection, spread of anaesthesia. doi: 10.3329/bjog.v23i1.3052 Bangladesh J Obstet Gynaecol, 2008; Vol. 23(1) : 15-19